Pengembangan Media Pembelajaran Wordwall Berbasis Game Edukasi Pada Mata Pelajaran IPS Kelas VI SDN 48 Cakranegara - Anugrah, Aldi; Istiningsih, Siti; Zain, Moh. Irawan (Pendagogia: Jurnal Pendidikan Dasar, 2022)
The problem that occurs in class VI of SDN 48 Cakranegara is that teachers rarely use learning media, especially learning media that smells of technology in ASEAN learning materials. The research aims to (1) find out how to make educational game-based Wordwall learning media for sixth graders in social studies, (2) find out educational game-based Wordwall learning media for VI elementary school students. This type of research is Research and Development (R&D) using the ADDIE development model with 5 stages, namely analysis, design, development, and implementation. The data collection technique used is using a material expert validation questionnaire, media expert validation questionnaire, and student response questionnaire. Data analysis used qualitative data analysis and quantitative data analysis. The results of this research and development are Wordwall learning media based on educational games, Wordwall learning media in social studies subjects. Based on the assessment of the media expert validator, the criteria are very feasible with an average percentage of 86% and material experts. Criteria are very feasible with a percentage of 96%. The results of the small group trial in stage I got very good criteria with an average of 96% and stage II got very decent criteria with an average percentage of 98%. Therefore, the educational game-based Wordwall learning media is suitable for use in social studies learning.